Pengaruh Penyusutan Temu Putih (Curcuma zedoaria (Berg) Roscoe) Terhadap Karakteristik Pengeringan Lapisan Tipis - Inge Scorpi Tulliza; Armansyah H. Tambunan; Usman Ahmad (Jurnal Keteknikan Pertanian, 2010)
Abstract The objective of this study is to analyze the occurrence of shrinkage during thin layer drying of Temu Putih (Curcuma zedoaria (Berg) Roscoe) and its effects to the drying characteristics. The experiments were conducted using a laboratory scale dryer with data acquisition and equipped with machine vision system.The drying conditions was controlled at temperatures (T) of 50°C, 60°C, 70°C,relative humidity (RH) 20%,30%, 40%, 50% and air velocity 0.78 m/s – 1.95 m/s with a specific combinations. The results show that the temu putih’s slices were shrinking as the moisture content was decreasing with almost linier correlation.The drying data was used to determine the drying constants using three models, namely Henderson andPabis, Lewis, and Page model. The effects of the shrinkage to the drying characteristics is discussed in term of the relation between surface area ratio (AR) to moisture ratio (MR). Keywords: Drying;Thin Layer drying; Shrinkage; Temu Putih Diterima: 24 Maret 2010; Disetujui: 13 September 2010